The Effect of Collaborative Learning Model on Improving PPKN Learning Outcomes and Social Attitudes in Elementary School Students - Nadia Salsabila; Diana Setiana; Wahyu Triono (Journal of Educational Sciences, 2026)
This study investigates the effect of the collaborative learning model on improving PPKN (Civic Education) learning outcomes and social attitudes of fifth grade students at SDN 2 Kemantren, Cirebon Regency. The study employed a quasi experimental design with a pretest-posttest control group framework involving 30 students divided equally into an experimental group (n=15) and a control group (n=15). The collaborative learning model was implemented over four meetings during May 2026. Data were collected using a 20-item multiple-choice test for learning outcomes and an observation sheet for social attitudes. Instrument validity and reliability were confirmed using Pearson product-moment correlation, Cronbach's Alpha (α = 0.845), and Cohen's Kappa (κ = 0.807). Independent Samples T-Test showed significant differences in posttest scores for learning outcomes and social attitudes (p = 0.000). MANOVA also confirmed a significant simultaneous effect (F = 190.434, Wilks' Lambda = 0.066, p = 0.000, Partial η² = 0.934). N-Gain scores indicated moderately effective improvement in both variables. PPKN teachers at the elementary level are therefore encouraged to adopt collaborative learning as a core instructional strategy to simultaneously improve students’ academic achievement and social character formation.